BIO-HYDROGEN PRODUCTION FROM TROPICAL BIOMASS FOR SUSTAINABLE ENERGY RESOURCES - Imai, Tsuyoshi; Hasyim, Rafiani (Journal of Techno-Social, 2016)
The fermentative process of tropical biomass has found to yield hydrogen (H2) and high rates of bacterial growth. Sago starch is commonly used in the making of many starchy food and beverages products. In general, many sago factories are located near rivers and straits where the risk of wastewater to be discharged. Therefore this study aims to investigate the fermentation of sago starch performed in different forms which can reduce the environmental impacts and recover the energy lost in the waste stream. Sago starches from Bengkalis, Indonesia were cultivated under moderate and extreme condition which includes pH, concentration and microbial community parameters for the H2 production test. The sago fermentation in the enrichment culture shows the increment of H2 yield by increasing the number of repeated batch cultivation. In addition, the highest hydrogen has been recovered when the pH is ranging from 6.5 to 8.0. This condition occurred when the acetic acid fermentation pathway was expected at the maximum level at 4 mol H2/mol glucose. This study confirmed that the highest H2 yields (maximum, 444.2 mg/g starchadded) can be observed when the starch concentration was sustained at the range of 2.5 to 15 g/L. Gelatinized dry starch was found to produce the highest H2 yield (157.3 mL H2/g starchadded) when compared to gelatinized wet starch, non-gelatinized dry starch and non-gelatinized wet starch. A denaturing-gradient-gel-electrophoresis (DGGE) shows no significant differences profiles from the four types of sago starch. However, all of the sago starch mixed culture show the present of Thermoanerobacterium at 49 52% GC except from the non-gelatinized wet starch mixed culture. In addition, no archeal cells have been observed in the mixture by 16S rRNA nested PCR detection method. The result of the microbial detection and the higher yield of H2 from the gelatinized sago starch cultures indicated that gelatinized culture contains microorganism that able to simultaneously degrade starch and produce H2 efficiently.